The Effects of NT-1044, a Novel AMPK Activator, on Endometrial Cancer Cell Proliferation, Apoptosis, Cell Stress and In Vivo Tumor Growth - Roque, Dario R.; Zhang, Lu; Wysham, Weiya Z.; Han, Jianjun; Sun, Wenchuan; Yin, Yajie; Livingston, James N.; Batchelor, Ken W.; Zhou, Chunxiao; Bae-Jump, Victoria L. (Frontiers in Oncology, 2021)
Objectives: Anti-diabetic biguanide drugs such as metformin may have anti-tumorigenic effects by behaving as AMPK activators and mTOR inhibitors. Metformin requires organic cation transporters (OCTs) for entry into cells, and NT-1044 is an AMPK activator designed to have greater affinity for two of these transporters, OCT1 and OCT3. We sought to compare the effects of NT-1044 on cell proliferation in human endometrial cancer (EC) cell lines and on tumor growth in an endometrioid EC mouse model. Methods: Cell proliferation was assessed in two EC cell lines, ECC-1 and Ishikawa, by MTT assay after exposure to NT-1044 for 72 hours of treatment. Apoptosis was analyzed by Annexin V-FITC and cleaved caspase 3 assays. Cell cycle progression was evaluated by Cellometer. Reactive oxygen species (ROS) were measured using DCFH-DA and JC-1 assays. For the in vivo studies, we utilized the LKB1fl/flp53fl/fl mouse model of endometrioid endometrial cancer. Mice were treated with placebo or NT-1044 or metformin (200 mg/kg/day, oral gavage) following tumor onset for 4 weeks. Results: NT-1044 and metformin significantly inhibited cell proliferation in a dose-dependent manner in both EC cell lines after 72 hours of exposure (IC50 218 μM for ECC-1; 87 μM for Ishikawa). Treatment with NT-1044 resulted in G1 cell cycle arrest, induced apoptosis and increased ROS production in both cell lines. NT-1044 increased phosphorylation of AMPK and decreased phosphorylation of S6, a key downstream target of the mTOR pathway. Expression of the cell cycle proteins CDK4, CDK6 and cyclin D1 decreased in a dose-dependent fashion while cellular stress protein expression was induced in both cell lines. As compared to placebo, NT-1044 and metformin inhibited endometrial tumor weight in obese and lean LKB1fl/flp53fl/fl mice. Conclusions: NT-1044 suppressed EC cell growth through G1 cell cycle arrest, induction of apoptosis and cellular stress, activation of AMPK and inhibition of the mTOR pathway. In addition, NT-1044 inhibited EC tumor growth in vivo under obese and lean conditions. More work is needed to determine if this novel biguanide will be beneficial in the treatment of women with EC, a disease strongly impacted by obesity and diabetes.